Comprehensive description of new and known stages of Americabaetis titthion Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae) - Amaral, Igor Ferreira; Salles, Frederico Falcão (Zootaxa, 2024)
The male imago of Americabaetis titthion is described for the first time. It can be distinguished from other male imagos of the genus by the following combination of characteristics: turbinate portion of the eyes with upper surface ellipsoidal and separated by approximately the width of a lateral ocellus; costal area of fore wings tinged with reddish-brown; presence of pairs of soft, setose protuberances on the meso- and metasternum; subgenital plate slightly concave; forceps with segment I/II slightly tapering medioapically. Supplementary descriptions for the nymph and female imago are provided, as well as the first description of the eggs of a species of the genus.